Design and simulation of techniques for mitigation of harmonic distortion in a three-phase rectifier (2020)
Rectifiers are electrical devices that receive an alternating signal and deliver a direct current signal at their output, this process by which they transform one type of energy to another is known as rectification. This type of device incorporates a phenomenon called harmonic distortion into the electrical network, which consists of malformations presented in the waveform of the alternating signal from which it feeds, which generate unwanted effects on electrical systems. Because of this, this work presents the combination of two harmonic distortion mitigation strategies (12-pulse multilevel converter and harmonic frequency tuned filtering stage) in order to reduce total harmonic distortion levels generated by a three-phase rectifier. © Published under licence by IOP Publishing Ltd.